Characteristics of Brain White Matter Microstructure in HIV Male Patients With Primary Syphilis Co-Infection - Qi, Yu; Li, Rui-Li; Wang, Yuan-Yuan; Wang, Wei; Liu, Xu-Ze; Liu, Jing; Li, Xing; Zhang, Xiao-Dong; Yu, Wen; Liu, Jiao-Jiao; Guo, Yi-Fan; Rao, Bo; et al. (Frontiers in Neurology, 2022)
Purpose To investigate the effect of syphilis infection on the microstructure of white matter (WM) in HIV-infected male patients using diffusion tensor imaging (DTI). Methods Twenty-seven HIV-infected male patients with current syphilis or a history of syphilis (HIV+/syphilis+), twenty-nine HIV-infected male patients without syphilis co-infection(HIV+/syphilis-) and twenty-nine healthy controls(HC) were enrolled. All participants received DTI and all patients received comprehensive neuropsychological assessment. Tract-based spatial statistics (TBSS) was adopted to analyze the DTI metrics: fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD). Correlation analysis was conducted to investigate the relationships between DTI metrics and cognitive performance. Results There were no significant differences in DTI measures between HIV+/syphilis- and HC. Compared with HC, lower FA were found in body of corpus callosum (BCC), splenium of corpus callosum (SCC), genu of corpus callosum (GCC), the bilateral anterior corona radiata (ACR), SCR, posterior corona radiata (PCR) and posterior thalamic radiation (PTR) in HIV+/syphilis+(P<0.05), Higher RD were found in BCC and SCC(p<0.05). Compared with HIV+/syphilis-, lower scores was found in complex motor skills (CMS) in HIV+/syphilis+, lower FA was found in BCC, SCC, GCC, the bilateral ACR, SCR, PCR, PTR, cingulate gyrus (CGC), the right inferior fronto-occipital fasciculus(IFO), retrolenticular part of internalcapsule (RLIC), sagittal stratum (SS), external capsule (EC) in HIV+/syphilis+(P<0.01). There was a significant positive correlation between FA in GCC and CMS, FA in BCC and CMS in HIV+/syphilis+. Conclusions Syphilis co-infection can have an additive or synergistic effect on the brain WM in HIV-infected subjects. Patients with syphilis and HIV co-infection should strengthen clinical and serological follow-up.